Mouth opening variables amongst the North Indian population - Disha Dixit; Pavitra Rastogi; Nand Lal; Rameshwari Singhal (Journal of Oral Biology and Craniofacial Research)
Background: For the clinician to conveniently perform an extensive oral examination, it is required to have a known normal range of maximum mouth opening (MMO). This study aims to establish a standard for calculating the normal range of mouth opening in the adult population of North India. The results of this research will have clinical implications for the treatment and diagnosis of diseases that affect the mouth opening in adults, either directly or indirectly. Aim: To evaluate mean mouth opening in North Indian population and establish their correlation with age and gender. Method: 662 adults from North Indian population, 317 males and 345 females in the age range of 18–80 years were evaluated on their consent. Maximum mouth opening was measured using calibrated vernier calliper scale. This study was conducted in the Department of Periodontology, Faculty of Dental Sciences, King George Medical University, Lucknow. Results: Males exhibited a higher mean MMO of 48.0 mm compared to females, who had a lower mean MMO of 45.1 mm among North Indian population of the country. In the statistical comparison of MMO between males and females within each age group, the results showed no significant differences. Conclusion: Mouth opening of females is less than males in all age groups and it seems to decrease with age in all age groups in both males and females. The variability of MMO with age appears statistically similar for both genders.